Development and validation of a jam-making module for adolescents with developmental delays - Abadam, Ma. Teresa R. (2009)
Three experts evaluated the contents of the jam-making module at the Special Education Department in Quezon City aimed at developing and validating a jam-making module for adolescents with developmental delays (ADD). Results showed that the jam-making module meets satisfactorily the criteria of good and effective components of the module: objectives, activities, ingredients and instructions as evaluated by the experts. The study concluded that the jam-making module is a valid, effective, and useful vocational program for ADHD. There was a significant progress in work skills, work behaviors, cognitive skills and interest and independence during the implementation of the module. The problems encountered were related to language deficit, discrimination and handling of dangerous equipment.